Fostering student empowerment for cultivating future leaders: a concept paper - Chia Sze Yee,; Wan Amsyar Hadie Wan Mahadi,; Muhammad Shahrulazmi Hashim,; Mohd Nuriman Mohd Ridzuan,; Meor Luqman Nur Haqeem Mohd Asri,; Amirah 'Azizah Badrul Hisham,; Puteri Khairunnissaq Mat Lazim,; Noratika Efendi,; Muhamad Zaid Irfan Mohd Norlizaiman,; Khalid Isa,; Mohd Faisal Hushim,; Zolhafizi Jaidi,; et al. (Penerbit Universiti Kebangsaan Malaysia, 2024)
This paper explores the practical implementation of student autonomy in higher education institutions, focusing on financial and activity management autonomy, student engagement in politics, and establishing platforms like the Student Parliament and Leadership Camps. The study, set in selected public universities in Malaysia, specifically Universiti Malaya, Universiti Kebangsaan Malaysia (UKM), Universiti Islam Antarabangsa Malaysia (UIAM), and Universiti Tun Hussein Onn Malaysia (UTHM), delves into the transformative impact of these initiatives on cultivating future leaders. The shift towards decentralised structures empowers students to take ownership of their education, fostering responsibility, collaboration, and innovation. Financial autonomy cultivates essential skills such as financial literacy and strategic planning while entrusting students with activity management nurtures event planning proficiency and teamwork. Engagement in politics, both on and off campus, develops civic responsibility and critical thinking. The Student Parliament and Leadership Camps provide forums for skills development, and involving strategic partners widens horizons. These initiatives collectively contribute to moulding a new generation of well-rounded leaders who are academically proficient, empathetic, and prepared to address global challenges, laying the foundation for a brighter future and a more enlightened and empowered society.